Epidemiology and long-term outcome in outpatients with chronic heart failure in Northwestern Europe. Issue 16 (21st February 2019) - Fröhlich, Hanna; Rosenfeld, Niklas; Täger, Tobias; Goode, Kevin; Kazmi, Syed; Hole, Torstein; Katus, Hugo A; Atar, Dan; Cleland, John G F; Agewall, Stefan; Clark, Andrew L; Frankenstein, Lutz; et al.
Abstract : Objective: To describe the epidemiology, long-term outcomes and temporal trends in mortality in ambulatory patients with chronic heart failure (HF) with reduced (HFrEF), mid-range (HFmrEF) or preserved ejection fraction (HFpEF) from three European countries. Methods: We identified 10 312 patients from the Norwegian HF Registry and the HF registries of the universities of Heidelberg, Germany, and Hull, UK. Patients were classified according to baseline left ventricular ejection fraction (LVEF) and time of enrolment (period 1: 1995–2005 vs period 2: 2006–2015). Predictors of mortality were analysed by use of univariable and multivariable Cox regression analyses. Results: Among 10 312 patients with stable HF, 7080 (68.7%), 2086 (20.2%) and 1146 (11.1%) were classified as having HFrEF, HFmrEF or HFpEF, respectively. A total of 4617 (44.8%) patients were included in period 1, and 5695 (55.2%) patients were included in period 2. Baseline characteristics significantly differed with respect to type of HF and time of enrolment. During a median follow-up of 66 (33–105) months, 5297 patients (51.4%) died. In multivariable analyses, survival was independent of LVEF category (p>0.05), while mortality was lower in period 2 as compared with period 1 (HR 0.81, 95% CI 0.72 to 0.91, p<0.001). Significant predictors of all-cause mortality regardless of HF category were increasing age, New York Heart Association functional class, N-terminal pro-brain natriuretic peptide and use of loop diuretics. Conclusion: Ambulatory patients with HF stratified by LVEF represent different phenotypes. However, after adjusting for a wide range of covariates, long-term survival is independent of LVEF category. Outcome significantly improved during the last two decades irrespective from type of HF.